On the Determinants of Size-Constancy in a Virtual Environment - Luo, Xun; Kenyon, Robert V.; Kamper, Derek G.; Sandin, Daniel J/; DeFanti, Thomas A. (International Journal of Virtual Reality, 2009)
An important aspect of a subjects perception of virtual objects in a virtual environment is whether the size of the object is perceived as it would be in the physical world, which is named size-constancy. The ability of subjects to appreciate size-constancy in an immersive virtual environment was studied while scene complexity, stereovision and motion parallax visual factors were manipulated resulting in twelve different viewing conditions. Under each visual condition, 18 subjects made size judgments of a virtual object displayed at five different distances from them. Responses from the majority of our population demonstrated that scene complexity and stereovision have a significant impact on subjects’ ability to appreciate size-constancy. In contrast, motion parallax produced by moving the virtual environment or by the movements of the observer alone proved not to be a significant factor in determining size-constancy performance. Consequently, size-constancy is best obtained when scene complexity and stereovision are components of the viewing conditions.